PHOSPHATE FERTILIZATION IMPROVE PRODUCTIVITY AND CHEMICAL-BROMATOLOGICAL COMPOSITION OF LEAF BLADE OF UNBURNED PASTURE - da Silva, Luiz Carlos; Lobo, Francisco de Almeida (Seven Editora, 2026)
We evaluate the effects of phosphate fertilization on the leaf blade productivity of unburned Brachiaria brizantha, cv. Marandu, as well its chemical-bromatological composition compared to the pasture burning in the southwestern Amazon. Brazilian Amazon has one of the highest proportion of planted pastures in Brazil and the Brachiaria brizantha is the most used species. The burning is an important factor that lead to the gradual degradation of pastures. These circumstances generate pastures with low capability of providing feed for cattle farming. The improvement caused by burnings occurs only in short periods after burning. Some alternative sources with a low content of soluble P, in turn, increases biomass productivity and the nutritional value of cultivated species. A field experiment was carried out in a completely randomized blocks design. The treatments consisted of unburned pasture treated with 0, 25, 100 and 200 kg ha-1 of P compared to the pasture burning. After applying the treatments, the pasture was desiccated in order to homogenize the plant emergence and growth after the period without rain from July to September. The dose of 100 kg ha-1 of P for unburned pasture promoted better productivity and mineral nutrient concentrations, and leaf quality for animal consumption was improved. Values of acid detergent fiber, neutral detergent fiber, lignin and crude protein indicate an adequate bromatological composition of leaf for animal consumption at 56 days of growth. The practical and theoretical implications of this research are discussed, providing insights into how the results can be applied or influence practices in the field of pasture management without fire using. These implications could encompass on how to apply and how much of an alternative phosphate must be applied to the soil to supply phosphorus for B. brizantha instead of using fire in the pasture management. This study contributes to the literature by highlighting the superiority of phosphorus application from alternative sources allied to N and K fertilization compared to the pasture burning practice in the Southwestern Amazon. This innovative approach can be used as a base for new researches and applied in the level of cattle farmers.DOI: https://doi.org/10.56238/sevened2026.008-083